Alexithymia, depression and anxiety in parents of children with neurodevelopmental disorder: Comparative study of autistic disorder, pervasive developmental disorder not otherwise specified and attention deficit–hyperactivity disorder. Issue 3 (26th February 2018) - Durukan, İbrahim; Kara, Koray; Almbaideen, Mahmoud; Karaman, Dursun; Gül, Hesna
Abstract: Background: Recent studies have shown that individuals with neurodevelopmental disorders and their relatives have problems expressing and recognizing emotions, but there is a lack of studies on alexithymia, and the relationship between parental alexithymia and depression–anxiety symptoms in these groups. The aim of this study was therefore to measure alexithymia, depression, and anxiety levels in parents of children with pervasive developmental disorders and attention deficit–hyperactivity disorder (ADHD), and determine whether there is a positive correlation between the child's neurodevelopmental problem severity and parent scores. Methods: Parents of 29 autistic disorder (AD), 28 pervasive developmental disorder not otherwise specified (PDD‐NOS) and 29 ADHD children were recruited into the study, and completed a demographic information form, as well as the Toronto Alexithymia Scale (TAS‐20), Beck Depression Inventory, and State–Trait Anxiety Inventory. Results: Alexithymia symptoms were higher in parents of children with AD than in others but unexpectedly, also these symptoms were higher in ADHD parents than in PDD‐NOS groups. In addition, there were unexpected differences according to alexithymia subtype, while only the difference in maternal TAS‐1 scores (difficulty in describing feelings) were statistically significant. Parental depression and state anxiety scores were increased as the child's symptom severity increased, but trait anxiety symptoms were higher in the AD and ADHD group than in the PDD‐NOS group. In all groups, maternal depression and anxiety scores were higher than paternal scores, and differences were significant for depression and anxiety types in AD, and for only anxiety types in ADHD parents. The AD group had the strongest correlation between parental depression–anxiety and alexithymia. Conclusion: The possibility of alexithymia, depression and anxiety should be kept in mind when working with parents of children with neurodevelopmental disorders.